2000
DOI: 10.1258/0956462001916119
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for HIV infection among asymptomatic pregnant women attending an antenatal clinic in western Kenya

Abstract: Our objective was to evaluate HIV prevalence and identify risk factors for HIV infection among women attending the antenatal clinic (ANC) at a large public hospital in Kisumu town, western Kenya. Between June 1996 and November 1997, in the context of a study to determine the effect of placental malaria on mother-to-child transmission of HIV in western Kenya, HIV-1 antibody testing was offered to women with a singleton uncomplicated pregnancy of > or =32 weeks' gestation attending the ANC. Women were interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 20 publications
1
53
0
Order By: Relevance
“…Strong associations between substance use and sexual risk behaviours have been reported previously and include smoking, drinking, and drug use being associated with sexual risk behaviours in general (Duncan, Strycker, & Duncan, 1999; Jackson, Sweeting, & Haw, 2012; Tu, Lou, Gao, Li, & Zabin, 2012), early sexual debut (Lowry et al, 1994), and number of sexual partners (Lowry et al, 1994; Shrier, Emans, Woods, & DuRant, 1997). Binge drinking has been associated with a higher number of partners (Guo et al, 2002), while more generally alcohol consumption has been associated with sexual debut, multiple sexual partners, and unprotected sex, all of which lead to an increased risk of HIV infection (Ayisi et al, 2000; Bassett et al, 1996; Clift et al, 2003; Lewis et al, 2005; Mnyika, Klepp, Kvale, & Ole-King’Ori, 1997; Myer, Mathews, & Little, 2002; Somsé, Chapko, & Hawkins, 1993; Zachariah et al, 2003). The increased risk of HIV infection may be attributable to the social consequences of substance use, which facilitates unprotected sex.…”
Section: Discussionmentioning
confidence: 99%
“…Strong associations between substance use and sexual risk behaviours have been reported previously and include smoking, drinking, and drug use being associated with sexual risk behaviours in general (Duncan, Strycker, & Duncan, 1999; Jackson, Sweeting, & Haw, 2012; Tu, Lou, Gao, Li, & Zabin, 2012), early sexual debut (Lowry et al, 1994), and number of sexual partners (Lowry et al, 1994; Shrier, Emans, Woods, & DuRant, 1997). Binge drinking has been associated with a higher number of partners (Guo et al, 2002), while more generally alcohol consumption has been associated with sexual debut, multiple sexual partners, and unprotected sex, all of which lead to an increased risk of HIV infection (Ayisi et al, 2000; Bassett et al, 1996; Clift et al, 2003; Lewis et al, 2005; Mnyika, Klepp, Kvale, & Ole-King’Ori, 1997; Myer, Mathews, & Little, 2002; Somsé, Chapko, & Hawkins, 1993; Zachariah et al, 2003). The increased risk of HIV infection may be attributable to the social consequences of substance use, which facilitates unprotected sex.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies were conducted among clinic/health facility attendees, and of these two studies conducted among pregnant women found that women who currently consumed alcohol were significantly more likely to be HIV+ than those who did not (Ayisi et al, 2000;Msuya et al, 2006). In addition, one of the studies found that women whose male partners consumed…”
Section: Discussionmentioning
confidence: 99%
“…In the context of an ongoing study to determine the effect of placental malaria on mother-to-child transmission of HIV, risk factors for HIV infection among asymptomatic women attending an antenatal clinic in Kisumu, western Kenya, were identified between June 1996 and November 1997 (Ayisi et al, 2000). HIV prevalence was 26.1% among the 2 844 women included in the final analysis, and a multivariate analysis found that reported alcohol consumption was independently associated with being HIV+ (adjusted RR 1.6, 95% CI: 1.1-2.5).…”
Section: Clinic/health Facility Attendeesmentioning
confidence: 99%
“…Of the 20 studies included in Fisher and colleagues' meta-analysis, 19 were retained for inclusion in the present study (Ao, Sam, Masenga, Seage, & Kapiga, 2006;Ayisi et al, 2000;Braddick et al, 1990;Demissie, Amre, & Tsega, 1996;Fritz et al, 2002;Hargreaves et al, 2002;Kapiga, Lyamuya, Lwihula, & Hunter, 1998;Kapiga et al, 2002;Kapiga et al, 2006;Lewis et al, 2005;Mbulaiteye et al, 2000;Mnyika, Klepp, Kvåle, & Ole-King'ori, 1996;Ndina-Achola et al, 1997;Sebit et al, 2003;Simbayi et al, 2004;Talbot et al, 2002;Tengia-Kessey, Msamanga, & Moshino, 1998;Zablotska et al, 2006;Zuma, Gouws, Williams, & Lurie, 2003) and one (Gilgen, Williams, & Campbell, 2000) was excluded for failing to meet the inclusion criteria specified below (i.e., it was not published in a peer-reviewed journal). An additional eight nonoverlapping studies published prior to 2009 were identified from our previous narrative review (Allen et al, 1992;Bassett et al, 1996;Clift et al, 2003;Dunkle et al, 2004;Fisher, Cook, Sam, & Kapiga, 2008;Msuya et al, 2006;St.…”
Section: Methods Literature Reviewmentioning
confidence: 99%